A retrospective clinical analysis of pediatric paragonimiasis in a Chinese children’s hospital from 2011 to 2019 - Manning Qian (Nature Portfolio, 2021)
Abstract Diagnosis of pediatric paragonimiasis is difficult because of its non-specific clinical manifestations. We retrospectively reviewed the records of pediatric paragonimiasis in Children’s Hospital of Fudan University from January 2011 to May 2019. The confirmed diagnosis of paragonimiasis was based on positive anti-parasite serological tests from the local Center for Disease Control (CDC). A total of 11 patients (mean age: 7.7 ± 3.1, male–female ratio: 7:4) diagnosed as paragonimiasis were included. 81.8% were from endemic areas such as Sichuan and Yunnan, and 36% had a clear history of raw crab or crayfish consumption. The characteristic clinical features of pediatric paragonimiasis were eosinophilia (100%), pleural effusion (81.8%), hepatomegaly (54.5%), ascites (54.5%), and subcutaneous nodules (45.5%). Misdiagnosed with other diseases including tuberculosis (18.2%), pneumonia (9.1%), intracranial space-occupying lesions (9.1%) and brain abcess (9.1%) led to rehospitalization and prolonged hospitalization. For treatment, a 3-day course of 150 mg/kg praziquantel (PZQ) didn’t show ideal treatment effectivity and 63.6% needed more than one course of PZQ, while triclabendazole in a total dose of 10 mg/kg had a better efficacy to stubborn manifestations. This study indicated that pediatric paragonimiasis was often misdiagnosed, and the treatment with a 3-day course of 150 mg/kg PZQ had a high rate of failure.